Utilitarian and Ideological Determinants of Attitudes towards Immigration: Germany Before and After the "Migration Crisis" - Heinz Welsch (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
Explanations of attitudes towards immigration include those that take a utilitarian perspective, focusing on immigration's real-world impacts, and others that look at immigration attitudes from the point of view of ideological affiliation. Focusing on the German "migration crisis" as a case study, this paper seeks to disentangle the roles of these types of explanation, placing an emphasis on possible connections between them. Specifically, the paper studies whether and to what extent perceptions of immigration impacts are related to people's ideological position through identity-protective cognition, implying an indirect channel through which ideology may shape attitudes toward immigration policies. Using data for 2014 – 2018, the paper finds that attitudes toward immigration were more strongly related to immigration's perceived economic and cultural impacts than to ideological position, even accounting for dependence of perceptions on ideology. Ideology-dependence of impact perceptions existed with respect to both economic and cultural impacts but was stronger with respect to the latter than the former. After the migration crisis, perceptions of economic impacts became less important in shaping immigration attitudes relative to perceptions of cultural impacts, and the latter became more ideology-dependent.
Keywords: F22; J15; O15; Z13; 330; Immigration; Identity; Cognition; Germany; Migration Crisis